1998
DOI: 10.1179/sur.1998.14.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Surface C Leaning Using Halogen Free Cleaning Agents: Surfactant Solutions and Hydrocarbon Solvents

Abstract: Minimising the health and environmental risks resulting from surface cleaning involves the design of suitable hardware but also the choice of a cleaning agent. As an alternative to chlorinated hydrocarbons, chlorine free hydrocarbons or surfactant cleaners in aqueous solution can be used. Whereas hydrocarbons work as solvents and remove mainly soluble oil or fat contamination, surfactant cleaners dissolve water soluble contamination and displace oils, fats, and insoluble particles, swarf, chippings, and cuttin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…All electrolytic cleaners contain a high percentage Figure 1. Synergistic action of builder (2 %) and surfactant (0.1 %) in degreasing [3] of alkali to provide high electrolyte conductivity.…”
Section: Cleaning and Degreasing In Aqueous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…All electrolytic cleaners contain a high percentage Figure 1. Synergistic action of builder (2 %) and surfactant (0.1 %) in degreasing [3] of alkali to provide high electrolyte conductivity.…”
Section: Cleaning and Degreasing In Aqueous Mediamentioning
confidence: 99%
“…Cleaning-agent concentration must be controlled in all baths. Diligent rinsing is crucial when aqueous, especially alkaline, cleaners are used, to remove nonvolatile cleaning-agent components which otherwise form milky-whitish layers or spots and can impede subsequent surface treatments [3].…”
Section: Cleaning Process Technologymentioning
confidence: 99%
“…The presence of residues generated by some of these products, such as sodium metasilicate Na 2 O 3 Si or borax Na 2 B 4 O 7 .10H 2 O, leads to a strong reduction of the adsorption of nitrogen. It was also shown that rinsing a part is essential in order to limit the presence of residues and to obtain conforming nitriding properties [21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%